Flavonoid from Stem Bark of Aquilaria microcarpa - A. N. Kristanti*, .- (Academy of Scientific Research and Technology Informatics Sector and Scientific Services National Information and Documentation Centre (NIDOC), 2018)
7-hydroxy-5,3’,4’-trimethoyflavon (1), a flavonoid, was isolated from stem bark of Aquilaria microcarpa, a species belonging to Thymelaeaceae that has not been investigated. The chemical structure has been elucidated based on spectroscopy FTIR, NMR and HRESI-MS analysis